Les Territoires de l’eau et la décentralisation. La gouvernance de bassin versant ou les limites d’une évidence - Stéphane Ghiotti (Développement Durable et Territoires)
The progressive implementation of territorial water policy in France, raises the stakes for water management in land planning and territorial development. The current vast movements in organisational and political reshuffling, support an operational approach by basin. However, it also contributes to establish the legitimacy of other territorial constructions - whose logic derives more from the strategic opportunism of local authorities than from the geographical and environmental dimensions of water. By side of “a” water territory, sits in fact, “many” water territories.